Analisis Profitabilitas Berdasarkan Teknik ROA, ROE, PM, BEP, CM PADA PT. Hanjaya Mandala Sampoerna Tbk - Hilwa Anggraini; Sri Sutandi; Masnoni; Irsan; Roy Saleh (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2017)
One of the tools used to know the company's financial condition is the financial statements. The financial statements describe the financial performance including the company's performance in generating profit. Interpretation of financial reporting can be done by measuring the ratio of the financial statements. This study aims to analyze the company's ability to generate profits through the analysis of financial statements through the level of profitability at PT. Hanjaya Mandala Sampoerna Tbk from 2011-2016. The data used is the financial statements of 2011-2016. Analysis technique using Profitability Ratio is ROA measurement, ROE, Profit Margin, BEP, and Margin Contribution. The result shows Profit Margin is good enough so that in every net sales Rp. 1.00 can generate net income. Return On Asset is productive so that the asset turnover Rp. 1.00 can generate net sales. Return On Equity is productive so that the average turnover of capital Rp. 1.00 can generate net income. Basic Earning Power is productive sothat the management of assets Rp. 1.00 can generate profit before tax. Margin contribution is good enough so that the management of assets Rp. 1.00 can generate gross profit.